Research on the precision forming cathode design method of electrochemical machining all-metal screw drill stator - Tang, Lin; Wang, Yi; Zhang, Jingjing; Zhang, Jun; Cao, Tong; Deng, Wen (International journal of advanced manufacturing technology, 2024)
In order to shorten the cathode design cycle, reduce design cost and improve forming accuracy for all-metal screw drill stator electrochemical machining (ECM), this paper proposed a precision forming cathode design method based on particle swarm optimization BP neural network (PSO-BP). The cathode design algorithm model of all-metal screw drill stator electrochemical machining was established, completed the camber feed cathode design. By using self-developed large scale horizontal CNC electrochemical machining equipment, under the condition of voltage 19 V, electrolyte 15%NaCl, electrolyte temperature 35 ± 1℃, electrolyte inlet pressure 1.6 MPa, and feed speed 10 mm/min, the stable and reliable electrochemical machining processing of the 4-m length of 38CrMoAlA all-metal screw drill stator was completed. The contour forming accuracy is ± 0.03 mm, and the surface roughness is Ra0.848 μm. Research showed that it is an efficient and feasible method to design the electrochemical machining camber feed cathode of all-metal screw drill stator using PSO-BP neural network.